The MARVEL Domain Protein Nce102 Regulates Actin Organization and Invasive Growth of Candida albicans - Lois M. Douglas (American Society for Microbiology, 2013)
ABSTRACT Invasive growth of the fungal pathogen Candida albicans into tissues promotes disseminated infections in humans. The plasma membrane is essential for pathogenesis because this important barrier mediates morphogenesis and invasive growth, as well as secretion of virulence factors, cell wall synthesis, nutrient import, and other processes. Previous studies showed that the Sur7 tetraspan protein that localizes to MCC (membrane compartment occupied by Can1)/eisosome subdomains of the plasma membrane regulates a broad range of key functions, including cell wall synthesis, morphogenesis, and resistance to copper. Therefore, a distinct tetraspan protein found in MCC/eisosomes, Nce102, was investigated. Nce102 belongs to the MARVEL domain protein family, which is implicated in regulating membrane structure and function. Deletion of NCE102 did not cause the broad defects seen in sur7Δ cells. Instead, the nce102Δ mutant displayed a unique phenotype in that it was defective in forming hyphae and invading low concentrations of agar but could invade well in higher agar concentrations. This phenotype was likely due to a defect in actin organization that was observed by phalloidin staining. In support of this, the invasive growth defect of a bni1Δ mutant that mislocalizes actin due to lack of the Bni1 formin was also reversed at high agar concentrations. This suggests that a denser matrix provides a signal that compensates for the actin defects. The nce102Δ mutant displayed decreased virulence and formed abnormal hyphae in mice. These studies identify novel ways that Nce102 and the physical environment surrounding C. albicans regulate morphogenesis and pathogenesis. IMPORTANCE The plasma membrane promotes virulence of the human fungal pathogen Candida albicans by acting as a protective barrier around the cell and mediating dynamic activities, such as morphogenesis, cell wall synthesis, secretion of virulence factors, and nutrient uptake. To better understand how the plasma membrane contributes to virulence, we analyzed a set of eight genes encoding MARVEL family proteins that are predicted to function in membrane organization. Interestingly, deletion of one gene, NCE102, caused a strong defect in formation of invasive hyphal growth in vitro and decreased virulence in mice. The nce102Δ mutant cells showed defects in actin organization that underlie the morphogenesis defect, since mutation of a known regulator of actin organization caused a similar defect. These studies identify a novel way in which the plasma membrane regulates the actin cytoskeleton and contributes to pathogenesis.